Modelling and control of induction based steam distillation essential oil extraction system using self-tuning fuzzy PID control / Zuraida Muhammad - Muhammad, Zuraida (Institute of Graduate Studies, UiTM, 2015)
Steam distillation is the most popular technique used in the industry for extraction of essential oil. The main contributing factors are the system cost, cleanliness, productivity, operational cost and the maintenance cost. In extracting the essential oils, several factors have been identified to have great influence on the extraction yields and quality. The extraction temperature is regarded as the most significant parameter that contributes to the amount of output yield and quality of oil. In conventional steam distillation system, electric heater or gas was commonly used as the heating source. However, some drawback was observed during application of electrical heater or gas and it’s also lacks of temperature control in order to satisfy the essential oil extraction process requirement…